One-pot synthesis of well-defined polyether/polyester block copolymers and terpolymers by a highly efficient catalyst switch approach. Issue 19 (27th April 2016) - Alamri, Haleema; Hadjichristidis, Nikos
Abstract : A novel catalyst switch methodology, which takes advantage of one of the best catalysts for epoxide ( t -BuP4 ) and cyclic ester ( t -BuP2 ) polymerization, is presented. Abstract : A highly efficient methodology, based on a novel catalyst switch approach with rapid crossover characteristics, was developed for the one-pot synthesis of block co/terpolymers of cyclic ethers and esters. This new approach, which takes advantage of one of the best catalysts for epoxide ( t -BuP4 ) and cyclic ester ( t -BuP2 ) polymerization, opens new horizons toward the synthesis of cyclic ether/ester complex macromolecular architectures.